(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the pragmatic aspects involved in translating compound words found in newspaper texts. Given the dynamic and context-sensitive nature of compounds in journalistic discourse, the study emphasizes the importance of considering not only the literal meaning but also the intended communicative effect, cultural nuances, and functional equivalence in the target language. The findings highlight that a pragmatic approach enhances the accuracy and effectiveness of translation by prioritizing the speaker’s intent and the reader’s comprehension in cross-cultural communication.